2017
DOI: 10.1186/s12859-017-1872-9
|View full text |Cite
|
Sign up to set email alerts
|

Identification of gene pairs through penalized regression subject to constraints

Abstract: BackgroundThis article concerns the identification of gene pairs or combinations of gene pairs associated with biological phenotype or clinical outcome, allowing for building predictive models that are not only robust to normalization but also easily validated and measured by qPCR techniques. However, given a small number of biological samples yet a large number of genes, this problem suffers from the difficulty of high computational complexity and imposes challenges to the accuracy of identification statistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Such ideal gene pairs are less likely to be observed purely due to technical biases, as this flip in expression is specific to subtype and is also replicated across many subjects. Indeed, many recent publications utilizing gene pair-based approaches have shown high accuracy and robustness in their validation datasets, reflecting this point (Afsari et al, 2015;Shen et al, 2017;Afsari et al, 2014;Leek, 2009;Kagaris et al, 2018;Patil et al, 2015).…”
Section: Methodsmentioning
confidence: 84%
“…Such ideal gene pairs are less likely to be observed purely due to technical biases, as this flip in expression is specific to subtype and is also replicated across many subjects. Indeed, many recent publications utilizing gene pair-based approaches have shown high accuracy and robustness in their validation datasets, reflecting this point (Afsari et al, 2015;Shen et al, 2017;Afsari et al, 2014;Leek, 2009;Kagaris et al, 2018;Patil et al, 2015).…”
Section: Methodsmentioning
confidence: 84%
“…Compared with predictors based on individual gene expressions, gene pair-based prognostic models have better normalizing robustness, predicting accuracy, and translational potential. 81 , 82 , 83 , 84 While recent studies have revealed the advantage of immune-related gene pairs in developing predictive signatures, 35 , 64 it remains statistically and computationally challenging to identify the best combination of gene pair signatures due to the quadratically combinatorial complexity. As we have demonstrated, TimiGP can be used to build effective prognostic models by focusing on marker gene pairs associated with cell-cell interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to predictors based on individual gene expressions, gene pair-based prognostic models have better normalizing robustness, predicting accuracy, and translational potential [73][74][75][76] . Despite this, it remains statistically and computationally challenging to identify the best combination of gene pair signatures due to the quadratically combinatorial complexity.…”
Section: Discussionmentioning
confidence: 99%